2018
DOI: 10.1183/13993003.00070-2018
|View full text |Cite
|
Sign up to set email alerts
|

Trend in rifampicin-, multidrug- and extensively drug-resistant tuberculosis in Italy, 2009–2016

Abstract: Tuberculosis (TB) caused by strains of Mycobacterium tuberculosis that are rifampicin-resistant (RR), multidrug-resistant (MDR) (strains resistant to at least isoniazid and rifampicin) or extensively drug-resistant (XDR) (MDR strains resistant to any fluoroquinolone (FQ) and to at least one second-line injectable drug (SLID): kanamycin, capreomycin or amikacin) is a major threat to TB control globally. All three groups require treatment with second-line drugs (SLDs) [1]. We previously reported that MDR-and XDR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Indeed, Namasivayam et al have studied the impact of tuberculosis (TB) antimicrobial treatment (each antibiotic alone and in combination) on the diversity and composition of the intestinal microbiota in infected mice, demonstrating the main role played by RF on anti‐TB treatment induced dysbiosis (Namasivayam et al, ). for the potential repercussions on the therapy of TB, when considering RF, the importance of this molecule as a cornerstone of TB therapy must take into account. In Italy (2009–2016), an increase in the number of RF‐resistant (RR) Mycobacterium tuberculosis strains has been recorded in foreign‐born persons (Eastern Europe, Former Soviet Unit, Sub‐Saharan Africa), whereas, if multidrug‐resistant (MDR) (strains resistant to at least isoniazid and RF) strains are considered, this phenomenon is evident both in Former Soviet Unit and Sub‐Saharan Africa‐born persons (Mustazzolu et al, ). In order to preserve RF (avoiding a further increase in RR strains), it is important not to use RF monotherapy (CL has no anti‐tuberculosis properties, although it may have activity against atypical mycobacteria) in patients with HS and unknown TB (latent tuberculosis infection [LTBI] or TB disease) simultaneously (Mendes‐Bastos et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, Namasivayam et al have studied the impact of tuberculosis (TB) antimicrobial treatment (each antibiotic alone and in combination) on the diversity and composition of the intestinal microbiota in infected mice, demonstrating the main role played by RF on anti‐TB treatment induced dysbiosis (Namasivayam et al, ). for the potential repercussions on the therapy of TB, when considering RF, the importance of this molecule as a cornerstone of TB therapy must take into account. In Italy (2009–2016), an increase in the number of RF‐resistant (RR) Mycobacterium tuberculosis strains has been recorded in foreign‐born persons (Eastern Europe, Former Soviet Unit, Sub‐Saharan Africa), whereas, if multidrug‐resistant (MDR) (strains resistant to at least isoniazid and RF) strains are considered, this phenomenon is evident both in Former Soviet Unit and Sub‐Saharan Africa‐born persons (Mustazzolu et al, ). In order to preserve RF (avoiding a further increase in RR strains), it is important not to use RF monotherapy (CL has no anti‐tuberculosis properties, although it may have activity against atypical mycobacteria) in patients with HS and unknown TB (latent tuberculosis infection [LTBI] or TB disease) simultaneously (Mendes‐Bastos et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…(responsible for CL metabolism) (Sousa, Pozniak, & Boffito, 2008 (Mustazzolu et al, 2018). In order to preserve RF (avoiding a further increase in RR strains), it is important not to use RF monotherapy (CL has no anti-tuberculosis properties, although it may have activity against atypical mycobacteria) in patients with HS and unknown TB (latent tuberculosis infection [LTBI] or TB disease) simultaneously (Mendes-Bastos et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In a study recently published by Mustazzoli et al18 based, as our study, on culture-confirmed TB and phenotypic DST results collected during approximately the same period (2009–2016) in the whole country, 54.7% of TB cases in Italy were of foreign origin and 4.4% of these were MDR (3% in the overall TB population). Similarly to our results, the MDR cases presented in the national study were mostly from East European countries, although they found the highest rates of patients born in Ukraine.…”
Section: Discussionmentioning
confidence: 85%
“…At the global level, 3.4% of new cases (patients never treated with anti-TB medicines, or treated for < 1 month) and 18% of previously treated cases (patients treated for ≥ 1 month in the past) had MDR/RR-TB, with the highest proportion occurring in the former Soviet Union (FSU) countries. In the low incidence countries of the European Economic Area, the MDR-TB was more prevalent among migrants (particularly from the FSU) than the native population [4,5].…”
Section: Epidemiology Of Drug Resistant Tbmentioning
confidence: 99%